(untitled) (Medico Legal Update, 2020)
This study was conducted to evaluate the negative effects of Tamoxifen (TAM) on Testis tissues and spermatogenesis. Use for this purpose forty male of mature albino rats were divided into 4 equal groups, 3 groups were administrated different doses (30, 40, 50) mg/kg b.w of TAM for 10 weeks as well as control group administrated with physiological solution (normal saline 0.9%). Histopathological examination of testes tissues in TAM groups showed histological changes that increased with the increased dose compared to control group include degeneration change were appeared as atrophy, deformity and destruction of the seminiferous tubules, congestion of blood vessels in the interstitial tissue and many seminiferous tubules, Also the results showed a significant different in the numbers of spermatogonia, primary spermatocytes cells and spermatiods. As noted in the results, the higher the dose, the lower the sperm production, and consequently the tissue injury increases.